2021
DOI: 10.1002/mame.202100226
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Optimal Fabrication, and Physico‐Mechanical Property Evaluation of PCL‐b‐PLLA Diblock Copolymer‐Based Nanoscale Roughness Textured Electrospun Mats

Abstract: Poly(ɛ-caprolactone)-block-poly(L-lactide) (PCL-b-PLLA) diblock copolymer and its electrospun mats (EMs) are characterized for their microstructural, thermal, and physico-mechanical properties. The EMs of synthesized copolymer exhibiting the optimal level of average fiber diameter (Co-FD) and diameter variation (Co-SD) are obtained following Taguchi's design of experiments (DOE). Electrospinning process parameters such as solution concentration, DMF content in CF/DMF solvent mixture, and applied voltage are va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Among many methods, chemical modi cation is considered to be an important way to expand the application of PLA-based materials, because it can effectively control the mechanical properties of PLA-based materials through structure and composition. 24, 25 Genovese et al 26 synthesized novel poly(lactic acid)-based chain-extended ABA triblock copolymers, where A is poly(lactic acid) and B is a synthetic random biobased aliphatic copolyester poly(propylene/neopentyl glycol succinate). The results found that compared with PLLA, the synthesized materials exhibited a better mechanical properties, and it is possible to design a class of materials with peculiar and promising properties for food packaging by adjusting the mass A/B ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Among many methods, chemical modi cation is considered to be an important way to expand the application of PLA-based materials, because it can effectively control the mechanical properties of PLA-based materials through structure and composition. 24, 25 Genovese et al 26 synthesized novel poly(lactic acid)-based chain-extended ABA triblock copolymers, where A is poly(lactic acid) and B is a synthetic random biobased aliphatic copolyester poly(propylene/neopentyl glycol succinate). The results found that compared with PLLA, the synthesized materials exhibited a better mechanical properties, and it is possible to design a class of materials with peculiar and promising properties for food packaging by adjusting the mass A/B ratio.…”
Section: Introductionmentioning
confidence: 99%